Distribution and Sources of Polycyclic Aromatic Hydrocarbons in Selected Landfill Sites - Kho, Hiaw Geik (2005)
Polycyclic aromatic hydrocarbons are one of the most important classes of anthropogenic micro-organic pollutants that had long been of interest in the field of environmental chemistry due to the fact that a small fraction of PAHs generated and released to environment by human activities had been shown to be carcinogenic and mutagenic to mammals. Polycyclic aromatic hydrocarbons have also been reported to disrupt endocrine system in humans. Upon entering the aquatic system. PAHs partition into few different phases namely truly dissolved, colloids, suspended particulate matter, surface sediments and biota. Landfilling and disposing of waste in open dumpsite had been expected to remain the most common and significant method for disposal of municipal solid wastes in Malaysia in near future. This study focuses on 3 landfill sites in Malaysia. The objectives of this study were to understand the distribution and sources of compound-specific PAHs in the landfill leachates and to determine their transport pathway to surrounding water bodies. The distribution of PAHs between various phases was the fbndamental in the control of ... 111 their movement and impact to the environment. Results from this study revealed that most of the particulate phase samples showed the higher PAHs concentration as compared to dissolved phase indicating the hydrophobicity characteristic of individual PAHs. High abundance of higher molecular weight (HMW) PAHs in particulate phase river water from Ulu Maasop Landfill had indicated the origin of the PAHs was from pyrogenic source which could be attributed to the illegal waste burning. Particulate phase leachate from Taman Beringin Landfill shows a mixture of petrogenic and pyrogenic signature although there was dominance in petrogenic signature as evidenced in their lower molecular weightlhigher molecular weight ratio (LMWIHMW) of 2.21. 2.17 and 2.60. Illegal dumping of waste petroleum products could be one of the petrogenic sources entering the river. Therefore. it can be concluded that the sources of PAHs among all of the landfills in this study was a mixture of petrogenic and pyrogenic origin. Similarities in PAHs distribution profile in leachate, groundwater and river water for all landfills studied was a grave concern due to the fact that leachate may had been transported to those aquatic environment. The flow of leachates into water bodies will have to be stopped immediately in order to protect the health of our environments.